Thèses sur la tactique. [Signé: G. Zinoviev (Grigorij Evseevič Zinov'ev), N. Lenine (Nicolai Lenin, ps. de Vladimir Il'ič Ul'janov), L. Trotski (Lev Trockij (ps. de Lev Davidovič Bronštejn), N. Boukharine (Nikolaj Ivanovič Bucharin), K. Radek, L. Kamenev, ps. de Lev Borisovič Rozenfel'd] (Section de la Presse de l'Internationale Communiste, 1921)
Karl Radek is pseud. of Karl Berngardovič Sobelson.